2011
DOI: 10.1111/j.1365-2141.2011.08607.x
|View full text |Cite
|
Sign up to set email alerts
|

Histone H4 acetylation by immunohistochemistry and prognosis in relapsed acute lymphocytic leukaemia (ALL)

Abstract: Summary Histone H4 acetylation was examined by immunohistochemistry in patients with acute lymphocytic leukaemia (ALL) in first relapse. Univariate and multivariate models identified correlates of complete remission (CR) and overall survival (OS). No variables were associated with achievement of CR. In multivariate analysis, weak histone H4 acetylation [Hazard Ratio (HR) 2·20, 95% confidence interval (CI) 0·93–5·23, P = 0·07], shorter interval from diagnosis to relapse (<9 vs. 9–24 vs. >24 months) (HR 1·82, 95… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…HDAC3, 7, and 9 upregulation has been linked to a poor prognosis in childhood ALL [ 99 , 101 ]. H4 acetylation has been suggested as a prognostic marker in newly diagnosed ALL or in recently relapsed patients with higher levels of H4 acetylation, as its associated with an increased overall survival [ 102 , 103 ]. HDAC3 has been shown to be recruited to the retinoic acid receptor beta (RARb) promoter as well as to the cytochrome P26 (CYP26) promoter by PML-RARα in APL [ 104 ].…”
Section: Histone Modifications In Hematological Malignanciesmentioning
confidence: 99%
“…HDAC3, 7, and 9 upregulation has been linked to a poor prognosis in childhood ALL [ 99 , 101 ]. H4 acetylation has been suggested as a prognostic marker in newly diagnosed ALL or in recently relapsed patients with higher levels of H4 acetylation, as its associated with an increased overall survival [ 102 , 103 ]. HDAC3 has been shown to be recruited to the retinoic acid receptor beta (RARb) promoter as well as to the cytochrome P26 (CYP26) promoter by PML-RARα in APL [ 104 ].…”
Section: Histone Modifications In Hematological Malignanciesmentioning
confidence: 99%
“…Among all HPTM, acetylation has a higher potential to promote chromatin decompaction, allowing transcription factors to access the DNA 15. Alterations in acetylation patterns result in transcriptional deregulation of several genes involved in the cell cycle and apoptosis, contributing to tumor initiation and progression 34. In oral cancer, dysregulation of histone acetylation has been associated with the activation of oncogenes by gain-of-function putative mechanism, but also to defects in DNA repair and checkpoints, this time by loss-of-function 30…”
Section: Discussionmentioning
confidence: 99%
“…15 Alterations in acetylation patterns result in transcriptional deregulation of several genes involved in the cell cycle and apoptosis, contributing to tumor initiation and progression. 34 In oral cancer, dysregulation of histone acetylation has been associated with the activation of oncogenes by gain-of-function putative mechanism, but also to defects in DNA repair and checkpoints, this time by loss-of-function. 30 On the other hand, histone deacetylation promotes genomic instability and increased proliferation through the silencing of tumor suppressor genes.…”
Section: Discussionmentioning
confidence: 99%
“…H4 acetylation was recently suggested as a prognostic marker in new ALL patients, as well as in patients at first relapse. Indeed, high levels of H4 acetylation were correlated with an increased overall survival, although the authors stated that the study has to be confirmed on a greater number of patients and adding the analysis of H3 acetylation levels [ 39 , 40 ].…”
Section: Reviewmentioning
confidence: 99%